2022
DOI: 10.3390/ma15134674
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Prediction of Laser Powder Bed Fusion Product Based on Melt Pool Radiation Intensity

Abstract: The quality stability and batch consistency of laser powder bed fusion products are key issues that must be solved in additive manufacturing. The melt pool radiation intensity data of laser powder bed fusion contain a significant amount of forming process information, and studies have shown that the analysis of melt pool radiation intensity using data-driven methods can achieve online quality judgment; however, there are still speed and accuracy problems. In this study, we propose a data-driven model for hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Subsequently, the data from Table 2 (groups d–g) were further subjected to a robust Random Forest Machine Learning (RF-ML) regression model, employing a supervised learning approach. This model was trained on labeled data, where the target variable was the measured channel surface roughness associated with each set of process parameters (laser power, scan speed, and layer thickness) to closely examine the interactions between the parameters [ 79 ] and to optimize with increased accuracy [ 80 , 81 ]. The RF-ML model employed in this study was meticulously developed through a series of carefully structured steps, beginning with data preprocessing.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the data from Table 2 (groups d–g) were further subjected to a robust Random Forest Machine Learning (RF-ML) regression model, employing a supervised learning approach. This model was trained on labeled data, where the target variable was the measured channel surface roughness associated with each set of process parameters (laser power, scan speed, and layer thickness) to closely examine the interactions between the parameters [ 79 ] and to optimize with increased accuracy [ 80 , 81 ]. The RF-ML model employed in this study was meticulously developed through a series of carefully structured steps, beginning with data preprocessing.…”
Section: Methodsmentioning
confidence: 99%
“…liquid surface [74], causing unstable melt pool flow and droplet splashing, increasing porosity and other defects. At the same time, metal vaporization causes volatile alloying elements to evaporate, resulting in alloy composition segregation, which affects the chemical composition, microstructure, and properties of the part [75].…”
Section: Mechanism Of Metal Evaporation In the Lpbf Processmentioning
confidence: 99%
“…The vapor expansion creates vapor recoil pressure on the molten surface [ 72 ], which increases its penetration depth and creates a gas-filled or plasma-filled depression, often referred to as a keyhole [ 51 ]. Porosity defects are caused by keyhole collapse, trapping shielding gas in the melt pool [ 73 ] and creating porosity defects, while the high saturation vapor pressure of alloying elements exerts recoil pressure on the melt pool liquid surface [ 74 ], causing unstable melt pool flow and droplet splashing, increasing porosity and other defects. At the same time, metal vaporization causes volatile alloying elements to evaporate, resulting in alloy composition segregation, which affects the chemical composition, microstructure, and properties of the part [ 75 ].…”
Section: Mechanism Of Metal Evaporation In the Lpbf Processmentioning
confidence: 99%
“…Experimental evaluation demonstrated that in-process sensing reduced the predicted root mean square error (RMSE) by 44% and improved the coefficient of determination (R 2 ) by 22.6% compared to a model that utilized only process parameters and material properties as inputs. Zhang et al [12] collected the melt pool radiation intensity data from the K438 powder printing process and processed this data to obtain nine features based on the power spectrum. These features were then combined with process parameter information (laser power, scan speed, scan pitch) and layer information to form the input features.…”
Section: Introductionmentioning
confidence: 99%